Alcohol consumption in Colombian university students - Betancourth Zambrano, Sonia; Tacán Bastidas, Lised Evelin; Córdoba Paz, Edwin Giovanny (Universidad y Salud, 2017)
Introduction: Alcohol consumption is conceived as a public health problem. Given the significant prevalence of consumption and its negative consequences, it is necessary to contribute to the prevention from the identification of populations at risk, such as the university, and the factors that influence the development of consumption. Objective: To identify and analyze the factors associated with alcohol consumption in university students from the South-western of Colombia. Materials and methods: A descriptive and cross-sectional study with a sample of 849 university students obtained by stratified random sampling was made. A questionnaire to characterize the consumption of alcohol and the sociodemographic factors was used for quantitative data collection. The analysis of the information included statistical descriptive for prevalence, consumption and polyconsumption pattern, as well as the relationship among the variables through the Chi-square test. Results: A prevalence of consumption of alcohol of 97.5% was found, most of the students reported consuming alcohol with their group of friends (76%), followed by the family (24.9%). The frequency of alcohol consumption is mainly given every month (25.8%) and every fifteen days (18.8%). In addition, associations between sex and the frequency of alcohol consumption (p=000), the number of type of alcoholic beverages (p= 000) were found, where the men are the ones who most consumed and who mainly mixed different types of beverages. Conclusions: Alcohol consumption levels are maintained over time and it is necessary that universities are concerned by an integral education which make it possible to reduce alcohol consumption.